Drifting space use of common cranes—Is there a mismatch between daytime behaviour and management?. (February 2018) - Nilsson, Lovisa; Aronsson, Malin; Persson, Jens; Månsson, Johan
Highlights: Crop damage caused by protected cranes raises the need for multi-objective management. We assessed space use and site fidelity of cranes equipped with GPS-transmitters. Cranes returned to daily activity areas but gradually shifted areas over time. We identified a mismatch in scale between space use and current preventive measures. Our findings improve crop damage mitigation and conservation of large grazing birds. Abstract: Many populations of large grazing birds (cranes, geese, swans) have recovered following protection. During migration, these birds often aggregate in large numbers at staging sites and feed on agricultural crops. Because staging sites often coincide with protected wetlands, extensive crop damages may avert both bird and wetland conservation. There is a need to integrate damage mitigation and conservation of large grazing birds staging in agricultural landscapes, based on knowledge of large grazing birds' spacing behavior. Their space use forms the basis for assessment of damage risk and for the scale at which measures should be implemented. We used high-resolution GPS location data to assess space use of common cranes (Grus grus) at an important staging site in south-central Sweden. We focus on daytime behaviour because this is the time when foraging cranes may cause crop damage and when preventive measures such as scaring and culling are conducted. We found that the daily activity area (mean 4.4 km 2 ) did not vary within staging periods. Cranes exhibited high site fidelity during staging, as their activity area over the staging period (mean 15.6 km 2 ) was considerably smaller than the entire staging site (>200 km 2 ). However, on a daily scale cranes gradually shifted activity areas, forming a space use pattern analogous to overlapping rings. This pattern is presumably explained by heterogeneous and unpredictable food availability caused by continuous changes in agricultural practices, weather conditions and competition. Considering the size of crane activity areas over the staging period and the scale of current damage preventive measures ( e.g., hunting permissions given for a few fields [mean size 0.049 km 2 ] at a time), we suggest that current preventive measures might be implemented on a too small scale compared to that of crane space use. Our findings highlight the necessity of adapting crop damage preventive measures to the scale of bird space use to facilitate both bird conservation and agricultural practices at wetlands staging sites along the flyways.